The change of bacterial spectrum after storage of X. Campestris pv. Campestris Inoculated Cabbage Heads (Brassica oleracea var. Capitata L.) - Ragasová, Lucia; Peňázová, Eliška; Gazdík, Filip; Pečenka, Jakub; Čechová, Jana; Pokluda, Robert; Baránek, Miroslav; Grzebelus, Dariusz; Eichmeier, Aleš (MDPI AG (Multidisciplinary Digital Publishing Institute-MDPI), 2020)
Changes in the bacterial spectrum of cabbage heads after storage under commonly used storage conditions were examined in this study. Cabbage seeds (Brassica oleracea var. capitata L.) were artificially inoculated with X. campestris pv. campestris (Xcc), a serious pathogen of cruciferous plants causing black rot. Isolation of bacterial cultures from Xcc-inoculated and non-inoculated cabbage heads were carried out in two time points-at the day of harvest and after four months of storage. According to our previous research and literature reports, the most frequent genera of bacteria were chosen for PCR testing, i.e., Bacillus cereus group, Bacillus subtilis group, Pseudomonas sp., and X. campestris pv. campestris. A few of the obtained bacterial cultures were negative for the four above-mentioned species. In those, other bacteria were identified by 16S rRNA sequencing. In both Xcc-inoculated and non-inoculated cabbage heads, changes of the bacterial spectrum over time were observed. The severity of Xcc infection of heads increased after four months of storage. Bacillus species represented the most frequently occurring bacterial genus. The presence of the Bacillus subtilis group increased significantly after storage in non-inoculated cabbage heads. The minor part of the other genera identified by sequencing in the first sampling were not detected in the stored cabbage heads. This was associated with a possible antagonistic behavior of Pseudomonas sp. and Bacillus sp.
Keywords: Bacillus; Black rot; Cabbage; Post-harvest; Pseudomonas; Sequencing; Storage; Vegetable